2011
DOI: 10.1097/cad.0b013e32833e0334
|View full text |Cite
|
Sign up to set email alerts
|

Canavanine augments proapoptotic effects of arginine deprivation in cultured human cancer cells

Abstract: Arginine deprivation achieved by means of recombinant arginine-degrading enzymes is currently being developed as a novel anticancer enzymotherapy. In this study, we showed that arginine deprivation in vitro profoundly and selectively sensitized human cancer cells of different organ origin to low doses of canavanine, an arginine analogue of plant origin. In sensitive cancer cells arginine starvation led to the activation of caspase-9, caspase-3 and caspase-7, cleavage of reparation enzyme, polyADP ribosyl polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 39 publications
(58 reference statements)
5
55
0
2
Order By: Relevance
“…In the opposite case, exogenous NO would rescue leukemic cells viability upon arginase treatment. This and other our studies on different cell models also support the notion that not arginine metabolism but other cell response signaling mechanisms must be potentially involved in determining cell fate upon arginine restriction [2,28].…”
Section: Resultssupporting
confidence: 63%
“…In the opposite case, exogenous NO would rescue leukemic cells viability upon arginase treatment. This and other our studies on different cell models also support the notion that not arginine metabolism but other cell response signaling mechanisms must be potentially involved in determining cell fate upon arginine restriction [2,28].…”
Section: Resultssupporting
confidence: 63%
“…We previously reported that the natural arginine analog canavanine potently enhances arginine deprivation-induced apoptosis in human cancer cells [23]. The impact of citrulline in this scenario is not yet known.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of arginine, canavanine not only induces programmed cell death in cancer cell subpopulations, but also severely interferes with growth recovery of the remaining membrane-intact cells after the termination of treatment [18, 23]. We therefore evaluated the impact of citrulline supplementation on the regrowth potential of arginine-starved, canavanine-treated CRC cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it has also been found more recently that canavanine could have important therapeutic properties. Thus, canavanine inhibits cell proliferation [20] and induces apoptosis [21,22] in cell cultures, and it also increases susceptibility to radiation in cancer cells [23]. In addition, it inhibits some of the deleterious effects of endotoxic shock in rat models [24,25] and has potential as an antidiabetic agent because it has been found to increase uptake of glucose [26] and release of insulin [27] in cell cultures.…”
Section: Speciesmentioning
confidence: 99%